Reducibility of nonlinear almost periodic systems of difference equations given on a torus - Martynyuk, D. I.; Perestyuk, N. A.; Samoilenko, A. M. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
Sufficient conditions are established for the reducibility of a nonlinear system of difference equations$$x(x + 1) = x(1) + ω + P(x(t), t) + λ,$$ where $P(x, t)$ is a function $2π$-periodic in $x_i(i = 1,..., n)$ and almost periodic in $t$ with a frequency basis $α$, to the system $$y(t + 1) = y(t) + ω.$$